Exploring mother-child relationships in the context of early environmental stressors - Moroney, Darren Michael (Curtin University, 2014)
This research project explored child externalising behaviour in a community sample and a clinically referred sample. Mothers contributed quantitative and qualitative data about their parenting behaviour and about their children’s behaviour. The findings revealed the need to consider child externalising behaviour as a potential consequence of emotion dysregulation that results from early trauma exposure and a non-optimal familial environments, characterised by a primary caregiver who struggles with reflective functioning and emotion coaching.